1966
DOI: 10.1037/h0082939
|View full text |Cite
|
Sign up to set email alerts
|

Habituation of the startle response and of heart rate in the rat.

Abstract: Male albino rats (9/group) were given an initial startle test followed by a second test at intervals of 1 day, 1, 2, 3, or 4 wk. A sixth (Habituation) group was exposed to the startle situation for 30 min./day for 7 days and then given 2 startle tests one day apart. Heart rate (HR) was also recorded in the startle situation. The Habituation group had significantly lower startle responses and HRs than the other 5 groups and showed habituation of HR both within and over days during the initial 7-day period. It w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

1972
1972
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 5 publications
4
12
0
Order By: Relevance
“…The freezing response, characterized by crouching and immobility, represents a conditional reaction of rats to conditional stimuli associated with aversive events (Blanchard & Blanchard, 1969;Bolles & Coltier, 1976;Fanselow, 1980). We have noted, as have others (e.g., Korn & Moyer, 1966;Martin & Miller, 1981), that during the early course of habituation training to an acoustic startle stimulus, rats exhibit freezing behavior. The influence of freezing on the rate of acoustic startle decrements has not, however, been systematically examined.…”
Section: Influence Of Long-term Sensitization On Long-term Habituatiosupporting
confidence: 81%
See 1 more Smart Citation
“…The freezing response, characterized by crouching and immobility, represents a conditional reaction of rats to conditional stimuli associated with aversive events (Blanchard & Blanchard, 1969;Bolles & Coltier, 1976;Fanselow, 1980). We have noted, as have others (e.g., Korn & Moyer, 1966;Martin & Miller, 1981), that during the early course of habituation training to an acoustic startle stimulus, rats exhibit freezing behavior. The influence of freezing on the rate of acoustic startle decrements has not, however, been systematically examined.…”
Section: Influence Of Long-term Sensitization On Long-term Habituatiosupporting
confidence: 81%
“…However, we have shown that it is the sensitization process and not the habituation process that is influenced by the manipulation of associative variables. Marlin and Miller (1981) and Korn and Moyer (1966) found that preexposure to the startle apparatus lowered the probability and amplitude of the acoustic startle response. Neither group evaluated long-term response decrements following preexposure, but both found no change in short-term decrements.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the US was now considered a complex of tonic and phasic cues, and response decrement to the US was considered to reflect habituation to the context plus habituation to the phasic stimulus (Korn & Moyer, 1966;Marlin & Miller, 1981). However, the increasing relevance ofcontext to habituation reached its zenith in the associative theory of habituation (Wagner, 1976(Wagner, , 1978(Wagner, , 1979.…”
Section: General Methods Animalsmentioning
confidence: 99%
“…Through behaviour, an animal may avoid a disturbance (for example by flying away) or habituate if a stimulus is perceived as harmless (Korn & Moyer 1966). Studies of responses of animals to aircraft have generally involved classifying observed behaviour into categories from non-response to startle (Brown 1990).…”
Section: Introductionmentioning
confidence: 99%